PERANCANGAN BUKU CERITA RAMAH SENSORIK ‘‘TIMUN MAS’’ UNTUK ANAK DENGAN SPEKTRUM AUTISME RINGAN - Salma Fadiyah; Ganis Resmisari (PT. Hasba Edukasi Mandiri, 2025)
Children with mild autism spectrum disorder often experience difficulties in understanding learning media that do not match their visual and sensory needs. This study aims to design a sensory-friendly interactive picture book based on Indonesian folktales for children aged 7–9 with mild autism. The method used is Human-Centered Design, involving observation, questionnaires, interviews, user needs analysis, and prototype development. The result is an interactive book featuring simple illustrations, soft colors, concise narration, and tactile elements such as textured surfaces and detachable components using velcro, tailored to the characteristics of children with mild autism.